Hypoxia-inducible factor 1α is Essential for Macrophage-mediated Erythroblast Proliferation in Acute Friend Retrovirus Infection. Issue 1 (December 2017) - Schreiber, Timm; Quinting, Theresa; Dittmer, Ulf; Fandrey, Joachim; Sutter, Kathrin
Abstract Macrophages are the frontline of defence against foreign microorganisms, including bacteria, parasites, and viruses. During acute viral infection, macrophages must invade the inflamed tissue toward low oxygen concentrations, where genetic cellular responses depend on hypoxia-inducible factors (HIF). In the study reported here we investigated the role of HIF-1α in macrophage function during acute retroviral infection. Wild-type and myeloid cell–specificHIF-1α knockout mice were infected with Friend retrovirus (FV), and immune response was analysed 7 and 10 days after infection. FV infection led to increased spleen weight in wild-type and knockout mice, whereas a profound proliferation of erythroblasts was seen only in wild-type mice. The number of spleen-infiltrating macrophages was also significantly lower in knockout animals. Macrophage invasion after FV infection in wild-type mice led to elevated amounts of activated macrophage-stimulating 1 protein that resulted in massive proliferation of erythrocyte precursor cells. This proliferation was absent from knockout mice because of impaired invasion capabilities of HIF-1α–deficient macrophages. Our study elucidated a novel mechanism of FV-induced erythrocyte precursor cell proliferation.